Oportunidades educativas y características familiares en Colombia: un análisis por cohortes (2014)
This paper aims to determine which family characteristics are correlated with access to postcompulsory education in Colombia. To do this, generalized ordered probit model is estimated using seven cohorts with data from the Household Integrated Survey (GEIH) for 2008-2012. The main econometric results show that characteristics such as parental education, employment status and socioeconomic status are correlated with the increase in the probability of choosing post-compulsory education in Colombia. Therefore, there are significant differences that show the existence of inequality in educational opportunities.